The Resourceful English Teacher: Some Reflections on Iraqi Teachers of English: مدرس اللغة الإنجليزية الحاذق: بعض التأملات في معلمي اللغة الإنجليزية العراقيين (مجلة ديالى للبحوث الانسانية, 2022)
Teaching is a dynamic process which entails a teacher to always strive for improving and developing his/her own personal and professional traits. His keeping in pace with the up-to-date pedagogical philosophies, methods and techniques will adhere to real success in his/her career. This is obviously shown in language teaching which requires continuous change and updating that is derived from consulting relevant books and other resources such as newspapers, magazines, plays, tales and use of technology like computer and internet. The teacher must keep abreast of the latest developments in the field of language teaching so as to implement them in his teaching practice.